Case report: Triple whammy: Synchronous radiotherapy induced glioblastoma multiforme and papillary thyroid cancer following nasopharyngeal carcinoma - Palaniandy, Kamalanathan; Kamarudin, Zalikha; Wong, Yin Ping; Mohamed Mukari, Shahizon Azura; Jiau, Winnie Xiao Hui; Bakar, Azizi Abu (Frontiers in Oncology, 2022)
Secondary malignancies following radiotherapy is well documented, with the estimated incidence of 5%. These may manifest as carcinomas, gliomas or sarcomas within the previous radiation field. Glioblastoma multiforme following radiotherapy for nasopharyngeal carcinoma is an uncommon occurrence and carries a poor prognosis. Whereas papillary thyroid carcinoma following radiotherapy is well documented, though the exact incidence is not well documented. The occurrence of synchronous radiotherapy induced malignancy over both sites has not been described in literature before. We describe a middle-aged gentleman diagnosed with glioblastoma multiforme and papillary thyroid carcinoma six years after radiotherapy for nasopharyngeal carcinoma. Though our case is the first reported case of synchronous tumour of its nature, it likely such cases are under reported. Long term vigilance for loco-regional radiotherapy induced secondary malignancies is a must and the presence of a second distinct secondary malignancy must be entertained.